The Urgency Of Formulating An Islamic Learning Theory As An Alternative To Modern Learning Theories - Qamariyah, Ummi Jamilatul; Ni'mah, Mamluatun; Firdaus, Achmad (International Journal of Learning and Instruction (IJLI), 2026)
This research seeks to analyze the critical need for developing an Islamic learning theory as a conceptual counterbalance to the prevailing influence of modern learning theories in educational settings, particularly within the context of Islamic Religious Education (IRE). The study adopts a library-based research approach by examining a wide range of scholarly sources, including Islamic education textbooks, national and international academic journal articles, and contemporary discussions addressing modern learning theories and the framework of tarbiyah Islamiyah. The results reveal that while behaviorist, cognitivist, constructivist, and humanist learning theories provide valuable methodological insights for instructional processes, the epistemological foundations upon which they are built largely secular and human-centered do not sufficiently address the spiritual, ethical, and transcendental dimensions that are central to Islamic educational philosophy. In addition, the study highlights a conceptual vacuum within Islamic education caused by the lack of a systematically articulated Islamic learning theory that is firmly rooted in the Islamic worldview, rather than derived through modification of Western theoretical models. Accordingly, this study emphasizes that constructing an Islamic learning theory represents a fundamental theoretical imperative, as it offers a framework that is more consistent with the aims of tarbiyah Islamiyah, particularly the cultivation of insan kamil through the balanced integration of cognitive, affective, spiritual, and moral elements. A well-formulated Islamic learning theory is therefore expected to function as a foundational reference for designing holistic, context-sensitive, and pedagogically coherent learning practices that reflect the distinctive nature of contemporary Islamic education.